PERCEPTION OF YOUNG CONSUMERS ON KHADI IN THE PANIPAT DISTRICT, HARYANA - MONIKA ROHILLA * and ANAMIKA GAUTAM (The Journal of Research ANGRAU, 2022)
The main aim of this research was to analyse the knowledge and awareness level of youthregarding the khadi fabric in the district of Panipat, Haryana. The study carried out the relationshipbetween characteristics of both buying behaviour and its acceptability among youth. A totalof 292adults, between the age of 18 and29 years, were selected as respondents. It was reported that 62%of youth, did not find khadi clothing a pocket-friendly option. It was seen that 40% of consumers wereaware of only cotton khadi and 56% accepted it for its high comfort value. Similarly, 70% of respondentsfelt that khadi fits all age groups. It was noticed that nearly 20% of youth were not using or buyingkhadi at all. It was also observed that nearly 20% of the respondents preferred khadi to be used inhome textiles only such as draperies, bed linens, blanket covers, etc.Whereas, 62% of youth feltkhadi clothing was expensive. It was concluded that consumers were having a positive attitude towardskhadi. It was noticed that along with comfort, youth prefer fashionable clothing that is relatively cheap.